Concrete capable of inhibiting concrete cracks

By using composite cement, high-temperature resistant aggregates and crack-resistant fibers, combined with the use of polymer emulsions and gas inducers, the problem of insufficient thermal resistance of concrete at high temperatures is solved, which significantly inhibits the generation of cracks and improves the concrete's Overall performance.

CN119462031AInactive Publication Date: 2025-02-18WENSHI LIAN CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411606238.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In high temperature weather, the thermal resistance of concrete is not high, resulting in large temperature differences between the internal and external, resulting in tensile stress, which in turn leads to concrete cracks and affects the stiffness and strength of the structure.

Method used

A new type of concrete that can inhibit concrete cracks are prepared through specific mixing and stirring processes.

Benefits of technology

It improves the tensile strength and toughness of concrete, reduces cracks caused by temperature difference, enhances the heat resistance and strength of concrete, and ensures the safety performance of building structures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119462031A_ABST
    Figure CN119462031A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of concrete, and discloses concrete capable of inhibiting concrete cracks, which is prepared from the following raw materials in parts by weight: 300 to 500 parts of composite cement, 1000 to 1200 parts of high-temperature-resistant aggregate, 500 to 550 parts of fine aggregate, 35 to 55 parts of anti-crack fiber, 3 to 5 parts of expanding agent, 3 to 5 parts of polymer emulsion, 100 to 150 parts of mineral powder, 5 to 7 parts of air entraining agent and 1 to 3 parts of high-efficiency water reducing agent. According to the invention, the composite cement is prepared by taking ordinary Portland cement as a base material and adding the Al2O3 cement, so that the high temperature resistance of the composite cement is enhanced; the strength and the stability of the concrete are maintained, meanwhile, the volume expansion caused by high temperature or the strength loss caused by too fast cement hydration reaction is reduced, the generation of cracks is further inhibited, and finally, the evaporation speed of water can be reduced through the use of the polymer emulsion and the air entraining agent; therefore, shrinkage cracks caused by too fast water loss are reduced, and the strength of the concrete is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of concrete, in particular to concrete capable of inhibiting concrete cracks. Background Art

[0002] Concrete is a building material made of cement, sand, gravel and water mixed in proportion. After hardening, it has properties such as pressure resistance, water resistance and fire resistance. It is one of the most widely used composite materials in civil engineering.

[0003] Due to its advantages such as high strength, good durability, low price and simple production process, concrete can not only withstand huge pressure and weight and maintain stable performance in various harsh environments, but also can be widely used in multiple construction fields. Its widespread use has greatly promoted the development and progress of human society and is an indispensable material in the construction of the modern world.

[0004] At present, with the continuous emergence of various large-scale structures, construction units have gradually increased their requirements for the quality of concrete. When facing such large structures, the larger the volume of concrete pouring, the more difficult it is for the heat inside to dissipate, especially in hot weather. The current concrete has low heat resistance, resulting in a large temperature difference between the inside and outside of the concrete. When the temperature difference is large, the expansion of the concrete is constrained by the outside, which will produce tensile stress. When the tensile stress exceeds the tensile strength of the concrete, the concrete will crack. The generation of such cracks will greatly affect the stiffness and strength of the structure, reducing the safety performance of the building, so it needs to be improved and optimized. Summary of the invention

[0005] The object of the present invention is to provide a concrete capable of suppressing concrete cracks, so as to solve the problems raised in the above-mentioned background technology.

[0006] In order to achieve the above-mentioned purpose, the present invention provides the following technical scheme: a concrete capable of inhibiting concrete cracks, comprising the following raw materials in parts by weight: 300-500 parts of composite cement, 1000-1200 parts of high temperature resistant aggregate, 500-550 parts of fine aggregate, 35-55 parts of anti-cracking fiber, 3-5 parts of expansion agent, 3-5 parts of polymer emulsion, 100-150 parts of mineral powder, 5-7 parts of air entraining agent and 1-3 parts of high-efficiency water reducer.

[0007] Preferably, the composite cement is based on ordinary Portland cement and is mixed with Al2O3 cement, the high temperature resistant aggregate is one of bauxite aggregate and refractory brick slag, the anti-cracking fiber includes steel fiber and polypropylene fiber, and the mineral powder is fly ash.

[0008] Preferably, the preparation process of the concrete is:

[0009] Step 1: dry material mixing, mixing the high temperature resistant aggregate and the fine aggregate, and mixing the prepared composite cement with the mineral powder;

[0010] Step 2, adding admixtures, adding polypropylene fiber and steel fiber to the mixture according to the ratio requirements, and adding expansion agent during the mixing process;

[0011] Step 3: Liquid addition: add water and high-efficiency water reducer according to the specified water-binder ratio, and finally add polymer emulsion and air entraining agent;

[0012] Step 4: wet mixing, ensure that all materials are added and then stirred by a forced mixer for 4-5 minutes at a speed of 20-30 rpm;

[0013] Step five: pouring and curing: pour the mixed concrete into the mold and cure for 28 days.

[0014] Preferably, the mixing ratio of the composite cement ordinary Portland cement and Al2O3 cement is 8:2, wherein the specific surface area of ​​the Portland cement is 300-400m 2 / kg, while the specific surface area of ​​Al2O3 cement is 300-350m 2 / kg.

[0015] Preferably, the particle size of the high temperature resistant aggregate is 5-40 mm, the fine aggregate is artificial sand, and the particle size of the fine aggregate is 1-5 mm.

[0016] Preferably, the ratio of steel fiber to polypropylene fiber in the anti-cracking fiber is 1:1, and the anti-cracking fiber needs to be mixed with dry materials evenly and then stirred with water to avoid agglomeration.

[0017] Preferably, during the addition of the admixture, the steel fiber has a length of 20-50 mm and a diameter of 0.2-0.8 mm; the polypropylene fiber has a length of 6-20 mm and a diameter of 0.03-0.1 mm. When the length is longer, the crack-resistant fiber needs to be sheared.

[0018] Preferably, the preparation process of the polymer emulsion is:

[0019] A1, uniformly mix water, emulsifier and stabilizer to complete the preparation of water phase;

[0020] A2, slowly adding the polymer monomer into the water phase while stirring;

[0021] A3, add initiator at a stable temperature between 60-80℃ to start the polymerization reaction. At this time, the polymer monomers polymerize into polymer chains. Under the action of the emulsifier, the polymer forms small particles and finally forms an emulsion.

[0022] Preferably, after the reaction is completed, the emulsion needs to be cooled and its properties such as viscosity and pH value need to be adjusted to ensure the stability and applicability of the emulsion.

[0023] The beneficial effects of the present invention are as follows:

[0024] 1. The present invention first prepares composite cement by using ordinary Portland cement as the base material and adding Al2O3 cement, so that the high temperature resistance of the composite cement is enhanced. By adding mineral powder, the strength and stability of the concrete are maintained while reducing the strength loss caused by the volume expansion caused by high temperature or the excessively fast cement hydration reaction, further inhibiting the generation of cracks. Finally, the evaporation rate of water can be reduced by using polymer emulsion and air entraining agent, thereby reducing the shrinkage cracks caused by excessively fast water loss, and effectively improving the strength of the concrete.

[0025] 2. The present invention greatly improves the tensile strength and toughness of concrete through the combined action of steel fiber and polypropylene fiber. The addition of expansion agent not only reduces cracks caused by temperature difference but also suppresses concrete cracks by strengthening the concrete itself. Compared with traditional concrete, this kind of concrete has high strength and good heat resistance. The expansion agent and anti-cracking fiber jointly realize the anti-cracking function. Finally, the water-cement ratio can be reduced by high-efficiency water reducer to ensure the fluidity of concrete.

[0026] 3. The present invention uses a suitable preparation method and a uniform stirring method to mix the raw materials of the concrete evenly to avoid agglomeration, and the bonding between the fiber and the cement matrix can enhance the toughness of the concrete. The performance of the concrete material can be fully exerted when used. In actual use, it can not only inhibit cracks, but also has the advantages of high strength and good fluidity, thereby improving the physical properties and safety performance of the product, and is highly versatile and applicable to most building structures. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a flow chart for preparing concrete according to the present invention. DETAILED DESCRIPTION

[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] like Figure 1As shown, an embodiment of the present invention provides a concrete capable of inhibiting concrete cracks, comprising the following raw materials in parts by weight: 300-500 parts of composite cement, 1000-1200 parts of high temperature resistant aggregate, 500-550 parts of fine aggregate, 35-55 parts of anti-cracking fiber, 3-5 parts of expansion agent, 3-5 parts of polymer emulsion, 100-150 parts of mineral powder, 5-7 parts of air entraining agent and 1-3 parts of high-efficiency water reducing agent.

[0030] First, composite cement is prepared by taking ordinary Portland cement as the base material and adding Al2O3 cement, so that the high temperature resistance of the composite cement is enhanced. While the addition of mineral powder maintains the strength and stability of the concrete, it reduces the volume expansion caused by high temperature or the strength loss caused by the excessively rapid cement hydration reaction, further inhibiting the generation of cracks. Finally, the use of polymer emulsion and air entraining agent can reduce the evaporation rate of water, thereby reducing the shrinkage cracks caused by excessively rapid water loss, and effectively improving the strength of the concrete.

[0031] The composite cement is based on ordinary silicate cement and is mixed with Al2O3 cement. The high temperature resistant aggregate is one of bauxite aggregate and refractory brick slag. The anti-cracking fiber includes steel fiber and polypropylene fiber. The mineral powder is fly ash.

[0032] Through the combined action of steel fiber and polypropylene fiber, the tensile strength and toughness of concrete are greatly improved. The addition of expansion agent not only reduces cracks caused by temperature difference but also suppresses concrete cracks by strengthening the concrete itself. Compared with traditional concrete, this type of concrete has high strength and good heat resistance. The expansion agent and anti-cracking fiber jointly realize the anti-cracking function. Finally, the water-cement ratio can be reduced by high-efficiency water reducer to ensure the fluidity of concrete.

[0033] The preparation process of the concrete is as follows:

[0034] Step 1: dry material mixing, mixing the high temperature resistant aggregate and the fine aggregate, and mixing the prepared composite cement with the mineral powder;

[0035] Mineral powder is an important admixture that can reduce the hydration heat of concrete and improve its workability and durability.

[0036] Step 2, adding admixtures, adding polypropylene fiber and steel fiber to the mixture according to the ratio requirements, and adding expansion agent during the mixing process;

[0037] The anti-cracking fibers are responsible for enhancing the toughness and strength of concrete, while the expansive agent produces micro-expansion during the cement hydration process, reducing cracks caused by temperature differences.

[0038] Step 3: Liquid addition: add water and high-efficiency water reducer according to the specified water-binder ratio, and finally add polymer emulsion and air entraining agent;

[0039] Polymer emulsion can form a protective film on the concrete surface to reduce water evaporation. Air entraining agent improves the frost resistance of concrete and can also reduce the rate of water evaporation in high temperature environments.

[0040] Step 4: wet mixing, ensure that all materials are added and then stirred by a forced mixer for 4-5 minutes at a speed of 20-30 rpm;

[0041] Ensure that all raw materials are in full contact with each other to avoid agglomeration, and adjust the amount of water according to the water-to-binder ratio during stirring.

[0042] Step five: pouring and curing: pour the mixed concrete into the mold and cure for 28 days.

[0043] During the curing stage, water should be sprayed to maintain moisture and ensure that the humidity range of the concrete is maintained.

[0044] Through appropriate preparation methods and uniform stirring methods, the raw materials of this type of concrete are mixed evenly to avoid agglomeration, and the bonding between the fiber and the cement matrix can enhance the toughness of the concrete. The performance of the concrete material can be fully utilized when used. In actual use, it can not only inhibit cracks, but also has the advantages of high strength and good fluidity, which improves the physical properties and safety performance of the product. It is highly versatile and can be applied to most building structures.

[0045] The mixing ratio of the composite cement, ordinary silicate cement and Al2O3 cement is 8:2, and the specific surface area of ​​silicate cement is 300-400m 2 / kg, while the specific surface area of ​​Al2O3 cement is 300-350m 2 / kg.

[0046] Al2O3 cement maintains good strength and structural stability at temperatures up to 1000°C and is suitable for concrete applications in high temperature environments. The addition of Al2O3 cement can improve the heat resistance of concrete.

[0047] Wherein, the particle size of the high temperature resistant aggregate is 5-40 mm, the fine aggregate is artificial sand, and the particle size of the fine aggregate is 1-5 mm.

[0048] High temperature resistant aggregate is bauxite aggregate. When there is refractory brick slag at the construction site, the refractory brick slag and bauxite aggregate can be replaced to save costs. Both have good stability and heat resistance at high temperatures. When the temperature inside the concrete cannot dissipate, the strength will not drop significantly.

[0049] The ratio of steel fiber to polypropylene fiber in the anti-cracking fiber is 1:1. The anti-cracking fiber needs to be mixed with dry materials evenly before adding water and stirring to avoid agglomeration.

[0050] Steel fibers can significantly enhance the tensile strength of concrete and reduce cracks caused by temperature and humidity changes. Polypropylene fibers also have good heat resistance and toughness. The combined effect of steel fibers and polypropylene fibers greatly improves the tensile strength and toughness of concrete, further inhibiting the occurrence of cracks.

[0051] Wherein, during the addition of the admixture, the length of the steel fiber is 20-50 mm, and the diameter is 0.2-0.8 mm; the length of the polypropylene fiber is 6-20 mm, and the diameter is 0.03-0.1 mm. When the length is longer, the crack-resistant fiber needs to be sheared.

[0052] The surface of the anti-cracking fiber needs to be cleaned and dried before mixing to ensure good bonding performance of the fiber and avoid agglomeration in the concrete.

[0053] Wherein, the preparation process of the polymer emulsion is:

[0054] A1, uniformly mix water, emulsifier and stabilizer to complete the preparation of water phase;

[0055] A2, slowly adding the polymer monomer into the water phase while stirring;

[0056] A3, add initiator at a stable temperature between 60-80℃ to start the polymerization reaction. At this time, the polymer monomers polymerize into polymer chains. Under the action of the emulsifier, the polymer forms small particles and finally forms an emulsion.

[0057] Among them, after the reaction is completed, the emulsion needs to be cooled and its viscosity, pH value and other properties need to be adjusted to ensure the stability and applicability of the emulsion.

[0058] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0059] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A concrete capable of suppressing concrete cracks, characterized in that: The material comprises the following raw materials in parts by weight: 300-500 parts of composite cement, 1000-1200 parts of high temperature resistant aggregate, 500-550 parts of fine aggregate, 35-55 parts of anti-cracking fiber, 3-5 parts of expansion agent, 3-5 parts of polymer emulsion, 100-150 parts of mineral powder, 5-7 parts of air entraining agent and 1-3 parts of high-efficiency water reducing agent.

2. The concrete capable of suppressing concrete cracks according to claim 1, characterized in that: The composite cement uses ordinary silicate cement as the base material and is mixed with Al2O3 cement. The high temperature resistant aggregate is one of bauxite aggregate and refractory brick slag. The anti-cracking fiber includes steel fiber and polypropylene fiber. The mineral powder is fly ash.

3. The concrete capable of suppressing concrete cracks according to claim 1, characterized in that: The preparation process of the concrete is as follows: Step 1: dry material mixing, mixing the high temperature resistant aggregate and the fine aggregate, and mixing the prepared composite cement with the mineral powder; Step 2, adding admixtures, adding polypropylene fiber and steel fiber to the mixture according to the ratio requirements, and adding expansion agent during the mixing process; Step 3: Liquid addition: add water and high-efficiency water reducer according to the specified water-binder ratio, and finally add polymer emulsion and air entraining agent; Step 4: wet mixing, ensure that all materials are added and then stirred by a forced mixer for 4-5 minutes at a speed of 20-30 rpm; Step five: pouring and curing: pour the mixed concrete into the mold and cure for 28 days.

4. The concrete capable of suppressing concrete cracks according to claim 1, characterized in that: The mixing ratio of the composite cement ordinary silicate cement and Al2O3 cement is 8:2, wherein the specific surface area of ​​silicate cement is 300-400m 2 / kg, while the specific surface area of ​​Al2O3 cement is 300-350m 2 / kg.

5. The concrete capable of suppressing concrete cracks according to claim 1, characterized in that: The particle size of the high temperature resistant aggregate is 5-40 mm, the fine aggregate is artificial sand, and the particle size of the fine aggregate is 1-5 mm.

6. The concrete capable of suppressing concrete cracks according to claim 1, characterized in that: The ratio of steel fiber to polypropylene fiber in the anti-cracking fiber is 1:

1. The anti-cracking fiber needs to be mixed with dry materials evenly and then stirred with water to avoid agglomeration.

7. The concrete capable of suppressing concrete cracks according to claim 3, characterized in that: During the addition of the admixture, the steel fiber has a length of 20-50 mm and a diameter of 0.2-0.8 mm; the polypropylene fiber has a length of 6-20 mm and a diameter of 0.03-0.1 mm. When the length is longer, the anti-cracking fiber needs to be sheared.

8. The concrete capable of suppressing concrete cracks according to claim 1, characterized in that: The preparation process of the polymer emulsion is as follows: A1, uniformly mix water, emulsifier and stabilizer to complete the preparation of water phase; A2, slowly adding the polymer monomer into the water phase while stirring; A3, add initiator at a stable temperature between 60-80℃ to start the polymerization reaction. At this time, the polymer monomers polymerize into polymer chains. Under the action of the emulsifier, the polymer forms small particles and finally forms an emulsion.

9. The concrete capable of suppressing concrete cracks according to claim 8, characterized in that: After the preparation reaction is completed, the emulsion needs to be cooled and its viscosity and pH value properties need to be adjusted to ensure the stability and applicability of the emulsion.